China-US trade dispute investigations and corporate earnings management strategy - Dongdong Li; Fan Shi; Kemin Wang (China Journal of Accounting Research, 2020)
This paper studies Chinese firms' earnings management strategy in response to the trade dispute investigations initiated by the U.S. from 2001 to 2018. This topic is important given the increasingly severe international trade environment and the significant influence of macro economy on financial reporting. We find that firms affected by the U.S.-initiated trade dispute investigations engage in more upward earnings management. Additionally, the result is more pronounced in firms with a more negative market reaction around the announcement of the investigations. Cross-sectional tests provide evidence that the positive relation is stronger among firms whose U.S. operating revenue and management ownership is high, firms in provinces with weak investor protection, and firms that performed well one year after initiation of the investigations. Moreover, investors react positively to the earnings management by the affected firms. Our results are robust to a variety of sensitivity checks. Overall, our findings suggest that companies will manage their earnings upward to mitigate the negative impacts of the U.S.-initiated trade dispute investigations.
Keywords: 650; China-US trade disputes; Earnings management; Market valuation